Formation of shear zone in Akebono Rock, Prince Olav Coast, East Antarctica - Baba, Sotaro; Hokada, Tomokazu; Kamei, Atsushi; Kitano, Ippei; Motoyoshi, Yoichi; Nantasin, Prayath; Setiawan, Nugroho; Dashbaatar, Davaa-ochir (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences, Wed. 5 Dec. / Entrance Hall (1st floor), National Institute of Polar Research conference object